2005
DOI: 10.1002/chem.200400298
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism of Porphyrin Metallation Studied by Theoretical Methods

Abstract: We have studied the reaction mechanism for the insertion of Mg2+ and Fe2+ into a porphyrin ring with density functional calculations with large basis set and including solvation, zero-point and thermal effects. We have followed the reaction from the outer-sphere complex, in which the metal is coordinated with six water molecules and the porphyrin is doubly protonated, until the metal ion is inserted into the deprotonated porphyrin ring with only one water ligand remaining. This reaction involves the stepwise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 66 publications
3
60
1
Order By: Relevance
“…Theoretical calculations predict that metallation involves a number of steps including removal of water from the metal ion annulus and deprotonation of the modified tetrapyrrole nitrogens (26). The binding of cobalt to the Se-CbiK His145, His207, and Glu175 triad promotes the desolvation steps.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical calculations predict that metallation involves a number of steps including removal of water from the metal ion annulus and deprotonation of the modified tetrapyrrole nitrogens (26). The binding of cobalt to the Se-CbiK His145, His207, and Glu175 triad promotes the desolvation steps.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in solution and with enzymatic systems led to the formulation of a general reaction mechanism for the metalation of porphyrins [12][13][14][15]. The steps for the mechanism include, first, deformation of the porphyrin ring; second, outer-sphere association of the solvated metal ion and the porphyrin; third, exchange of a coordinated solvent molecule with the first pyrrolenine nitrogen atom; fourth, chelate-ring closure with liberation of additional solvent molecules to form the 'sitting-atop complex'; fifth, first deprotonation of a pyrrole nitrogen atom; and last, deprotonation of the second pyrrole nitrogen with formation of the metalated porphyrin ( Figure Ib).…”
Section: Reaction Mechanism Of Porphyrin Metalationmentioning
confidence: 99%
“…Recently, Shen and Ryde [14] assessed the importance of ligand exchange in the non-enzymatic incorporation of either Fe 2+ or Mg 2+ into a porphyrin ring and found that the ligand-exchange step is rate limiting for the reaction. The estimated activation energies associated with this step were ~51 and 72 kJ/mol for Fe 2+ and Mg 2+ , respectively.…”
Section: Interplay Between Porphyrin Distortion and Metal Ion Specifimentioning
confidence: 99%
See 2 more Smart Citations